Artificial consortium that produces riboflavin regulates distribution of acetoin and 2,3‐butanediol by Paenibacillus polymyxa CJX518 - Liu, Lei (Eng Life Sci, 2017)
The introduction of an NADH/NAD(+) regeneration system can regulate the distribution between acetoin and 2,3‐butanediol. NADH regeneration can also enhance butanol production in coculture fermentation. In this work, a novel artificial consortium of Paenibacillus polymyxa CJX518 and recombinant Escherichia coli LS02T that produces riboflavin (VB(2)) was used to regulate the NADH/NAD(+) ratio and, consequently, the distribution of acetoin and 2,3‐butanediol by P. polymyxa. Compared with a pure culture of P. polymyxa, the level of acetoin was increased 76.7% in the P. polymyxa and recombinant E. coli coculture. Meanwhile, the maximum production and yield of acetoin in an artificial consortium with fed‐batch fermentation were 57.2 g/L and 0.4 g/g glucose, respectively. Additionally, the VB(2) production of recombinant E. coli could maintain a relatively low NADH/NAD(+) ratio by changing NADH dehydrogenase activity. It was also found that 2,3‐butanediol dehydrogenase activity was enhanced and improved acetoin production by the addition of exogenous VB(2) or by being in the artificial consortium that produces VB(2). These results illustrate that the coculture of P. polymyxa and recombinant E. coli has enormous potential to improve acetoin production. It was also a novel strategy to regulate the NADH/NAD(+) ratio to improve the acetoin production of P. polymyxa.